Anomalous temperature dependence of electrical resistivity in Mg0.6Zn0.4Fe2O4 ferrite - Mustafa Hj. Abdullah,; Ahmad Nazlim Yusoff, (Universiti Kebangsaan Malaysia, 1996)
The electrical resistivity of Mg0.6Zn0.4Fe2O4 ferrite was measured as a function of temperature in the range 300-630 K. Two anomalies are observed in the resistivity curves for measurements during heating up. These anomalies are identified as a magnetic anomaly at the Neel temperature, TN = 598 K, while the other one at TOt = 445 K is discussed as due to the contribution of conduction from the tetrahedral sites. The anomaly at Tot was reduced in the measurements during recooling, while the anomaly at TN was disappeared completely during recooling and second cycle. These effects are discussed as due to the increase of Fe2+ ions at the octahedral sites as a result of cation redistribution at higher temperatures. A relatively small anomaly at Tot still can be observed during the second run. This is possible if the Fe2+ ions have a preference to be relocated at the tetrahedral sites at lower temperatures.